Red capitalism : the fragile financial foundation of China's extraordinary rise - Walter, Carl E., 1947-; Howie, Fraser J. T. (Singapore ; Hoboken, NJ : Wiley, 2011)
It details how the Chinese government reformed and modeled its financial system in 30yrs since it began its policy of engagement with the west.
Looking back at the policy of reform and opening -- China's fortress banking system -- The fragile fortress -- China's captive bond market -- The struggle over China's bond markets -- Western finance, SOE reform and China's stock markets -- The national team and China's government --- The forbidden city.
Includes bibliographical references (p. 221-222) and index.
uaj 26/04/13
Loans
Keywords: Finance -- China; China -- Economic conditions -- 2000-; China -- Economic policy -- 2000-